Improving Community Economic Independence Through Downstreaming Andaliman Into Ready-To-Drink Juice Products - Siagian, Nalom; Siagian, Grace Angelia Julieta; Lubis, Rut Onike (International Journal of Economics (IJEC), 2025)
This Community Service (PKM) was carried out by lecturers and students of the Business Administration Study Program, Faculty of Social and Political Sciences, HKBP Nommensen University, Medan, Postgraduate Students of the Faculty of Economics, University of North Sumatra in collaboration with the Regional Management Board (DPD) of MARTABE North Sumatra, located at Jl. Until No. 260 Medan, MARTABE North Sumatra is a community that contributes ideas to develop North Sumatra Province in terms of creativity, community innovation as Martabe members to improve the household economy. This Community Service (PKM) was carried out with the aim of empowering the community in the MARTABE North Sumatra community as members. Through this PKM, the community as MARTABE members are given empowerment through training on how to process Andaliman raw materials with various other mixed ingredients so that they can be accepted by the market as quality drinks. This program is expected to be a sustainable solution for increasing the added value of Andaliman through processing it into functional beverage products. With strong processing and marketing skills, the community will achieve increased income and economic independence. Downstreaming andaliman into ready-to-drink juice is not simply a technical process, but a multidimensional intervention that combines food science, microeconomics, community empowerment, and marketing strategies. The program's success depends on an integrated approach: scientific product validation, human capacity building, a realistic business model, and regulatory compliance. With this foundation, this Community Service (PKM) program has the potential to generate tangible and sustainable economic impact for the MARTABE community members in North Sumatra